PENGGUNAAN CCTV (CLOSED CIRCUIT TELEVISION) SEBAGAI ALAT BUKTI PETUNJUK DALAM MENGUNGKAP TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR (Studi Pada Satreskrim Polres Sawahlunto) - Saputra, Ardiansyah Rolindo (Universitas Ekasakti, 2020)
The position of CCTV according to the ITE and RKUHAP Laws is a legitimate evidence, whereas according to the Criminal Procedure Code the position of CCTV is evidence but there is an expansion in the ITE Law article 5 paragraph (2) which states that electronic information or electronic documents or printouts are extensions of evidence which is valid in accordance with the applicable Procedural Law in Indonesia and the position of CCTV in proving a common crime in the trial is evidence, because the KUHAP does not regulate the position of CCTV as evidence. One of the facilities for using CCTV is the disclosure of criminal acts of motor vehicle theft which are very prevalent in the jurisdiction of the Sawahlunto Regional Police Station. This research is a descriptive analytical study. Adapaun the results of research into motor vehicle theft at the Sawahlunto police Satreskrim, there were 264 cases of theft of motorized vehicles that were revealed and recorded through CCTV from 509 criminal acts of motor vehicle theft that were reported at the Satal Police Headquarters in Sawalunto. The use of CCTV helps investigators to uncover who is the perpetrator of the crime of motor vehicle theft with the help of IT experts who understand CCTV. The elements that meet CCTV as evidence are Article 184 paragraph 1 of the Criminal Procedure Code, CCTV footage can be used as evidence of expansion (which is also strengthened by the Constitutional Court Decision No. 20 / PUU-XIV / 2016 dated September 7, 2016 and Article 5 of the Law ITE) so that CCTV footage can be used as a panel of judges as a guide to ensure the existence of a criminal act. Second, the constraints faced by Sawahlunto District Police Satreskrim investigators in using CCTV as evidence to reveal the crime of motor vehicle theft are maintaining CCTV in the original state, because after data from CCTV was taken, the video was not clearly visible when playing and brought CCTV experts nor can it be fast.